2001
DOI: 10.1046/j.1365-2036.2001.00949.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of mixed infections by Helicobacter pylori in Hong Kong: metronidazole sensitivity and overall genotype

Abstract: INTRODUCTIONHelicobacter pylori establishes long-term chronic infections in the human gastric mucosa that can lead to active chronic gastritis and peptic ulcer disease, and is an early risk factor for gastric adenocarcinoma and mucosa-associated lymphoid tissue lymphoma. 1±4 Metronidazole is frequently included as one component in multi-drug treatment regimens. However, the prevalence of metronidazole resistance in some populations is very high, and this decreases the overall success rate of metronidazole-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Further, it is possible to underestimate familial clustering by not investigating all strains that may theoretically infect an individual (40). In the presence of both shared and unique isolates, the number of shared strains will be underestimated if only the unique ones are examined.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is possible to underestimate familial clustering by not investigating all strains that may theoretically infect an individual (40). In the presence of both shared and unique isolates, the number of shared strains will be underestimated if only the unique ones are examined.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller number of patients (10 to 20%) have shown evidence of a mixed infection, defined as clones from a single patient that are more similar to isolates from other patients than they are to each other. Interestingly, strains isolated at the same time or after 6 months to 10 years have shown similar divergence (11,35,40,41,46,57). Thus, while populations may diverge within the host, divergence appears to occur slowly.…”
mentioning
confidence: 88%
“…Molecular fingerprinting studies using RAPD (57), amplified fragment length polymorphisms (AFLP) (40), and sequence analysis of virulence-associated or housekeeping genes (20,46) with multiple single-colony isolates or cultures obtained from separate biopsy samples from single patients revealed that strains isolated from single patients were closely related but that there were subtle differences in the majority of patients. The variants have even been referred to as quasispecies of a single strain (35).…”
mentioning
confidence: 99%
“…Genetic variations in this bacterium during its chronic infection can be one of the main causes of treatment failure through the emergence of newly evolved resistant H. pylori strains in each patient (9). However, this failure could also be caused by coinfection with diverse strains presenting different resistance phenotypes (2).…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori is a gram-negative, microaerophilic bacterium that was established as an etiological agent of chronic gastritis, peptic ulcer, mucosal-associated lymphoid tissue (MALT) lymphoma, and gastric cancer (1)(2)(3)(4). Greater than 50z of people in the world are infected with this bacterium (5).…”
Section: Introductionmentioning
confidence: 99%